Tapping the Culturati: An Underexploited Source of Private Finance for the Arts in Ireland - King, Timothy (Irish Journal of Arts Management and Cultural Policy, 2013)
The paper asks why cultural organizations in Ireland, in contrast to the UK, raise so little finance from private individuals, and in particular from those who go regularly to live performances or to galleries and museums. The rationale for cultural subsidies, including the offer of relief from income tax on the value of individual donations is reviewed and accepted. Income tax relief in Ireland has several unique features which probably explain why it has been such a limited source of finance. These include the high minimum value required for a donation to be eligible for tax relief, the administrative complexity of reclaiming tax on behalf of PAYE taxpayers, and the very restrictive interpretation of the tax legislation that is applied to determine a donation’s eligibility. Ways of overcoming these obstacles, in the light of changes announced in the December 2012 budget, are suggested. In particular, cooperation among cultural organizations could both facilitate the reclamation of income tax on donations and carry out cost-effective fundraising campaigns.